Odpowiedzi

2010-03-11T16:03:05+01:00
A) (-15):3-5*(-1)=-5-5*(-1)=-5+6= 11
b) 3*(-7)*(-2)=-21*(-2)=42
c) 6*(-4)+5*(-9)= -24+5*(-9)=-24-45=-21
d) 24-36/4-7=-12/-2=-10
e) -9-6/-3*(-4)= -9-6/+12=-3/+12 = 4
f) -9+5*(-11)/4-1=-9- 55/3= 64/3=21,(3)
g)4*-1-3/-2-3= -4-3/-2-3=-7/-7=1
1 5 1
2010-03-11T16:08:14+01:00
A) (-15):3-5*(-1)=-5+5=0
b) 3*(-7)*(-2)=-21-42=-63
c) 6*(-4)+5*(-9)=-24+(-45)=-69
d) 24-36/4-7=24-9-7=8
e) -9-6/-3*(-4)=-9-8=-17
f) -9+5*(-11)/4-1=-9+(-55)/4-1=-9+(-13,75)-1=-23,75
g)4*-1-3/-2-3=-4-1-(*1,5)-3=-5+1,5-3=-0,5

Myślę, że pomogłam
Pozdrowienia ;)
1 1 1